KIA (KITÂBAH ITU ASYIK): PENGEMBANGAN MULTIMEDIA BERBASIS ADOBE FLASH PROFESSIONAL CS6 PADA KETERAMPILAN MENULIS UNTUK SISWA KELAS X MA (Universitas Negeri Semarang, 2018)
The problems on Arabic learning writing skills are difficult and tedious learning because of the absence oflearning media. For that, we need to develop a learning media that can improve motivation of students. Theform of learning media is a multimedia. Furthermore, that multimedia is called KIA (Kitâbah Itu Asyik orwriting is fun). This multimedia is created by Adobe Flash Professional CS6 that is Adobe Systems' flagshipproduct. That purposes are: describe the requirements of teachers and students, KIA’s media design, andexperts validity of KIA’s products for Arabic writing skills for students of class X senior high school. The designis research and development (R&D) with steps: formulate the potential and problem, collect the informationand data, product design, product validity, and improve the product design. The conclusion of this study isteachers and students requires KIA’s media based on their requirements analysis. KIA’s media is made withadapted to the Arabic Curriculum on 2013 in the class X a year. The theme is consists of the initial appearanceof KIA’s media, title, apperception, KI/KD, material, evaluation, profile, direction, and exit. The results ofproduct validity is stated that